Biosynthesis of emulsan biopolymers from agro-based feedstocks - Panilaitis, B. (2007)
Aims: The need for biocompatible, biodegradable, and versatile biopolymers permeates many fields including environmental and food technology. The goal of the study presented here is to establish the utility of agricultural oils as an inexpensive carbon source to produce materials useful for biomedical materials and offer positive attributes in terms of green chemistry. Methods and Results: Structural variants of the complex acylated polysaccharide, emulsan, secreted from Acinetobacter venetianus RAG‐1, were biosynthesized in cultures supplemented with agricultural feedstocks to examine the feasibility of conversion of these substrates into value‐added biopolymers. Acinetobacter venetianus produced chemically and biologically distinct emulsan variants in culture on soy molasses and tallow oil. These variants possess significant biological function, including macrophage activation and adjuvant activity, in similar range to that observed for the standard emulsan formed on ethanol‐fed A. venetianus. Conclusions: The results indicate that this novel family of biopolymers can be produced in significant quantities from the readily available renewable agricultural feedstocks and the resulting structures and functions can be correlated to the chemistry of these feedstocks. Significance and Impact of the Study: The significant quantities of agricultural oils produced annually represent an untapped source for bioconversion to valuable products. The results of this study confirm that the important polymer emulsan can be synthesized from this inexpensive carbon source.